Pension reform during the demographic transition - Hans Fehr (University of Würzburg, Department of Economics, 1999)
Like in many other OECD countries, the population will age rapidly in Germany during the next decades. This undermines the future sustainability of the current unfunded public pension system and motivates the search for reform options. The present paper aimes to evaluate some currently discussed pension reform proposals. The numerical analysis is based on an extended overlapping-generations model which accounts for rising life expectancy and declining fertility in oder to replicate the demographic transition in Germany. Given the current unfunded pension system, the model first calculates a baseline path of the economy. Then it compares the macroeconomic impact as well as the distributional and efficiency effects of various reform measures such as partial funding and tax financed minimum pensions.
Keywords: H55; J26; 330; Population Ageing; Pension reform; overlapping-generations models; Rentenreform; Bevölkerungsökonomie; Overlapping Generations; Gesetzliche Rentenversicherung; Wirkungsanalyse; Wohlfahrtseffekt; Deutschland; Alternde Bevölkerung